Learning versus Working; Factors Affecting Adolescent Time Allocation in Pakistan (The Pakistan Development Review, 2012)
This paper explores how family, school and community factors influence adolescents’ time allocation among market work, domestic work, learning and leisure. We model adolescents’ time use in a multivariate framework, using explanatory variables characterising the household as well as labour demand, school access and school quality at the district level. This research shows that the amount of time children spend working, whether at home or in the market, is strongly correlated with household poverty, as proxied by an asset index. Consistent with the literature on the predictors of school enrolments of adolescents, the time spent on learning is also significantly lower among the poor. In Pakistan the Benazir Income Support Programme (BISP) census poverty score database, which includes information on household assets, would be a very promising tool to target efforts to increase children’s time allocated to learning. JEL classification: D60, I24, I30 Keywords: Pakistan, Education, Child Labour.